2010
DOI: 10.1136/qshc.2008.030114
|View full text |Cite
|
Sign up to set email alerts
|

Time to listen: a review of methods to solicit patient reports of adverse events

Abstract: Background Patients have been shown to report accurate observations of medical errors and adverse events. Various methods of introducing patient reporting into patient safety systems have been published with little consensus among researchers on the most effective method. Terminology for use in patient safety reporting has yet to be standardised. Methods Two databases, PubMed and MEDLINE, were searched for literature on patient reporting of medical errors and adverse events. Comparisons were performed to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 22 publications
4
119
0
4
Order By: Relevance
“…individual interviewing of hospitalised patients or conducting follow-up by telephone on patient experiences of using health services) can be most effective in increasing the amount of patient feedback [37]. Other studies have also shown the effectiveness of actively solicited patient feedback [37,62]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…individual interviewing of hospitalised patients or conducting follow-up by telephone on patient experiences of using health services) can be most effective in increasing the amount of patient feedback [37]. Other studies have also shown the effectiveness of actively solicited patient feedback [37,62]. …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a telephone survey in Israel revealed that, while 25% of the respondents had a cause to complain only 9.5% actually complained, and of these most complained informally [36]. However, when patients do complain their reporting of adverse events has been shown to be generally reliable [37]. We argue that health systems have a responsibility for identifying such emerging patterns [10] by analysing such data, and using these results for improving systems performance.…”
Section: Introductionmentioning
confidence: 99%
“…We do not yet know what other kind of events might be identifi ed as worthy of investigation by patients and families. What makes an event 'abnormal', and therefore a potential candidate for analysis, is a complex matter of surprise, rarity, intensity, severity and perhaps also the a basic feeling of the injustice of being Future reporting systems which seek to involve patients and families will need a balance of open-ended narratives and closed-ended questions for cause analysis and classifi cation (King et al 2010 ). Primary care patient reporting studies have used a combination of methods such as written, online or telephone reporting and telephone recruitment with a follow up in-person interview.…”
Section: Select Problems For Analysis Which Are Important To Patientsmentioning
confidence: 99%
“…Consumers should be involved in training of the health care workers. Two-way communication and honesty are keys to advancing understanding (2, 31, 34). …”
Section: Unique Patient Safety Issues In Neonatal Carementioning
confidence: 99%